Nepal-China Bilateral Economic Cooperation Empowering Nepalese Economy - Kharel, Khom Raj; Upadhyay, Yadav Mani; Kharel, Suman (Patan Pragya, 2021)
Bilateral economic cooperation is one of means for improving economic, social and political relations between two countries. Nepal and China have been enjoying good neighborly respects and benefit since the establishment of diplomatic relations in 1955. Both countries behave a good neighborhood relations and enjoyed fruitful bilateral cooperation and mutual support and following the social and economic development activities by exchanging cooperation in the areas of trade, tourism, investment and connectivity, building human capital and infrastructure and deepening people to people relations is at the center of Nepal-China bilateral relations. Within Nepal and China, there are marvelous possibilities promoting socio-economic transformation and raising the living standard of people through the mutual cooperation in the areas of mutual interest. Cooperation under the Belt and Road Initiative (BRI) is of great significance for Nepal and China. The present study is conducted with the aim of examining the economic impact of bilateral economic cooperation between Nepal and China. The impact of bilateral cooperation with China in Nepalese economy has been analyzed in terms of FDI flows, trade between Nepal, China and economic assistance from China to Nepal and tourists arrivals from China over the period of 2000-2019 by applying simple statistical tools and simple linear regression model. The results show that there have been positive influences on Nepalese economy with bilateral economic cooperation of China.